Chest drain aerosol generation in COVID-19 and emission reduction using a simple anti-viral filter. Issue 1 (4th November 2020) - Duffy, Clodagh; Kidd, Andrew; Francis, Sarah; Tsim, Selina; McNaughton, Laura; Ferguson, Katie; Ferguson, Jenny; Rodgers, K Gary; McGroarty, Claire; Sayer, Robin; Blyth, Kevin G
Abstract : Introduction: The COVID-19 pandemic has been characterised by significant in-hospital virus transmission and deaths among healthcare workers. Sources of in-hospital transmission are not fully understood, with special precautions currently reserved for procedures previously shown to generate aerosols (particles <5 μm). Pleural procedures are not currently considered AGPs (Aerosol Generating Procedures), reflecting a lack of data in this area. Methods: An underwater seal chest drain bottle (R54500, Rocket Medical UK) was set up inside a 60-litre plastic box and connected via an airtight conduit to a medical air supply. A multichannel particle counter (TSI Aerotrak 9310 Aerosol Monitor) was placed inside the box, allowing measurement of particle count/cubic foot (pc/ft 3 ) within six channel sizes: 0.3–0.5, 0.5–1, 1–3, 3–5, 5–10 and >10 μm. Stabilised particle counts at 1, 3 and 5 L/min were compared by Wilcoxon signed rank test; p values were Bonferroni-adjusted. Measurements were repeated with a simple anti-viral filter, designed using repurposed materials by the study team, attached to the drain bottle. The pressure within the bottle was measured to assess any effect of the filter on bottle function. Results: Aerosol emissions increased with increasing air flow, with the largest increase observed in smaller particles (0.3–3 μm). Concentration of the smallest particles (0.3–0.5 μm) increased from background levels by 700, 1400 and 2500 pc/ft 3 at 1, 3 and 5 L/min, respectively. However, dispersion of particles of all sizes was effectively prevented by use of the viral filter at all flow rates. Use of the filter was associated with a maximum pressure rise of 0.3 cm H2 O after 24 hours of flow at 5 L/min, suggesting minimal impact on drain function. Conclusion: A bubbling chest drain is a source of aerosolised particles, but emission can be prevented using a simple anti-viral filter. These data should be considered when designing measures to reduce in-hospital spread of SARS-CoV-2.